Clinical profile, complications, outcome and predictors of intensive care for paediatric scrub typhus: a tertiary hospital-based study from Southern Rajasthan, India - Vaishnav, Prerna; Shivpuri, Deepak (International Journal of Contemporary Pediatrics, 2024)
Background: Scrub typhus is an endemic acute febrile zoonotic disease and one of the most neglected tropical illnesses. In 2019, its outbreak was reported from Mewar region of Rajasthan, India. It is caused by Orientia tsutsugamushi which is intra cellular gram-negative coccobacilli. Methods: It is retrospective descriptive study conducted on children diagnosed positive for scrub typhus by IgM enzyme-linked immunosorbent assay (ELISA) admitted in ward and paediatric intensive care unit at tertiary care centre during 1 year of study period from April 2023 to March 2024. Clinical profile, laboratory parameters, course of illness and outcome data were collected in predesigned case records proforma for analysis. Results: Mean age of presentation was 10.5±3.2 years with female preponderance (F:M 1.21:1). 78.5% belong to rural areas. Environmental exposure was living close to forests, bushes in 38%, crop fields in 26% and cattle shed with pets in 30%. All cases had fever (100%, n=42) followed by vomiting (62%), cough-cold (42.8%), myalgia (40.4%), altered sensorium (35.7%), breathlessness (31%), oliguria (16.6%), conjunctival redness (11.9%). Most common signs were temperature >101’F (90.4%), hepatomegaly (62%), hypotension (21.4%), edema (23.8%), meningeal signs (14.2%). Tachypnoea (n=14) (p value <0.0001), CRT>3 seconds (n=13) (p value <0.0003), altered sensorium (n=15) (p value=0.0003) and SpO2 <90% (n=7) (p value=0.004) were found significant predictors of pediatric intensive care unit (PICU) admission. Eschar and rash seen in 3 cases (7.1%). 16 (38%) children requiring intensive care unit admission had statistically significant anaemia (85.7%) (p=0.013), thrombocytopenia (78.5%) (p=0.042) and raised C-reactive protein (CRP) (50%) (p<0.0001). Conclusions: Scrub typhus is common in Rajasthan and should be suspected in any child with acute febrile encephalopathy, signs of shock, breathlessness, hepatomegaly, anaemia and thrombocytopenia in the monsoon season with the history of exposure. Early diagnosis and prompt treatment with doxycycline can prevent mortality.